INTEGRATING ECOSYSTEM-BASED ADAPTATION (EBA) INTO SUSTAINABLE TROPICAL FOREST MANAGEMENT - Gia Bibilashvili; Mariam Kapanadze; Levan Kharabadze (Journal of Selvicoltura Asean, 2026)
Ecosystem-Based Adaptation (EbA) has emerged as a promising approach to enhancing the resilience of tropical forests against climate change impacts. As tropical forests are vital for biodiversity, climate regulation, and the livelihoods of millions, their sustainable management is crucial in addressing both environmental and socio-economic challenges. This research aims to integrate EbA principles into sustainable tropical forest management, exploring effective strategies that promote both ecological conservation and community adaptation. The study utilizes a mixed-methods approach, combining qualitative case studies and quantitative analysis of forest health indicators across various tropical regions. Data were gathered from forest management plans, stakeholder interviews, and remote sensing technology, focusing on key EbA strategies such as ecosystem restoration, sustainable land use practices, and community-based adaptation. The results highlight that integrating EbA into forest management significantly improves forest resilience, mitigates climate-related risks, and strengthens local adaptive capacity. Additionally, the study identifies barriers to implementation, including insufficient funding, policy gaps, and limited local engagement. In conclusion, EbA offers a holistic framework for tropical forest management that enhances ecosystem services while building community resilience. However, further research is needed to overcome existing challenges and scale up EbA practices across tropical regions.